The effect of vaginal and perineal massage with sesame oil compared with lubricant gel on the length of the second stage of labor and perineal rupture in nulliparous women: randomized clinical trial - Fatemeh Shushtaripour; Nahid Javadifar; Maryam Moradi; Mojgan Javadnoori; Fatemeh Amini (Mashhad University of Medical Sciences, 2022)
Introduction: Prolonged labor, especially the second stage, negatively affects labor outcomes. Previous studies reported different findings for the effect of lubricants such as oils and gel on vaginal delivery process and outcomes. The Iranian Traditional Medicine recommends massage with oils such as sesame oil to facilitate birth. This study was performed aimed to evaluate the effect of vaginal and perineal massage with sesame oil in comparison with lubricant gel on the duration of the second stage of labor, perineal damage and episiotomy in nulliparous women. Methods: This randomized clinical trial was performed in 2020 on 180 nulliparous women in Ahvaz. The subjects were randomly divided into three groups of sesame oil, lubricant gel, and control group (60 women in each group). In the Sesame oil group, perineal and vaginal massage was performed in the second stage of labor with 5 cc of sesame oil during vaginal examination. The gel group received the same massage with lubricant gel. The control group received only routine care. The duration of the second stage of labor and the frequency of perineal laceration and episiotomy were compared in three groups. Data were analyzed by SPSS (version 22) and covariance and chi-square test. P<0.05 was considered statistically significant. Results: There were no significant differences among the three groups in terms of demographic characteristics, perineal laceration, and episiotomy (P≥0.05). The duration of the second stage of labor was significantly shorter in the sesame oil group (32.60 ± 1.78 min) than the lubricant gel group (37.50 ±1.78 min) and the control group (44.92 ±78.1 min) (p <0.05). Conclusion: Vaginal and perineal massage with sesame oil can reduce the duration of the second stage of labor.